2021
DOI: 10.21511/bbs.16(4).2021.02
|View full text |Cite
|
Sign up to set email alerts
|

The impact of emotional intelligence, employee empowerment and cultural intelligence on commercial bank employees’ job satisfaction

Abstract: This paper aims to examine the impact of emotional intelligence (EQ), employee empowerment (EE), and cultural intelligence (CQ) on commercial bank employees’ job satisfaction in Bangladesh. For this purpose, a survey questionnaire was developed based on pre-tested constructs. The study used a convenience sampling technique, supplemented by a non-probability sampling method. 200 bank employees were invited to participate in the survey; finally, 130 responses were received as fully complete, with a 65% response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…It further reduces work stress and improves trust for the organization, which are very helpful for boosting up JS (Choi et al, 2016;Okello and Gilson, 2015). It make them feel that they are the owners of their work where they can use their creative thinking, experience and knowledge for enhancing their recognition at workplace that creates JS (Akhter et al, 2021;Francis and Alagas, 2019). According to Herzberg theory an individual gets satisfied if they are given chances to take initiatives and have higher authority, recognition, responsibility and personal growth at work that intrinsically motivates them resulting in JS (Byrne, 2006).…”
Section: Organizational Career Development Job Satisfaction and Emplo...mentioning
confidence: 97%
“…It further reduces work stress and improves trust for the organization, which are very helpful for boosting up JS (Choi et al, 2016;Okello and Gilson, 2015). It make them feel that they are the owners of their work where they can use their creative thinking, experience and knowledge for enhancing their recognition at workplace that creates JS (Akhter et al, 2021;Francis and Alagas, 2019). According to Herzberg theory an individual gets satisfied if they are given chances to take initiatives and have higher authority, recognition, responsibility and personal growth at work that intrinsically motivates them resulting in JS (Byrne, 2006).…”
Section: Organizational Career Development Job Satisfaction and Emplo...mentioning
confidence: 97%
“…An employee with a high employee satis-faction rate has a greater motivation to work. In contrast, an employee who has a low rate of employee satisfaction has a negative and low rate of behavior and motivation to work (Akhter et al, 2021).…”
Section: Literature Review and Hypothesesmentioning
confidence: 98%
“…The findings of Bano et al (2021) revealed that all dimensions of EI showed significant positive correlation with JS. Akhter et al (2021) showed that EI and CI had a positive effect on bank employees’ JS levels. Schlaegel et al (2022) found that EI dimensions were related to JS and investigated the structure of the EI-JS and EI-job performance relationship.…”
Section: Literature Reviewmentioning
confidence: 98%